Tourism Communication Strategy Model In Revitalizing Local Culture In Biak Numfor Papua - sudi, Mohamad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The purpose of this study is to determine the collaboration model of tourism communication strategies in revitalizing local culture in  Biak Numfor Papua Regency.  This research is  a descriptive research with a qualitative approach.  The data collection method used is the triangulation method by combining data collection techniques such as observation, in-depth interviews, and FGDs to analyze the potential for local culture-based tourism development.  The results showed that  the collaboration model Strategy applied to revitalize local culture  in Biak Numfor Papua in implementing tourism communication  programs   related to  the form of collaboration between actors  in tourism industry development policies in Biak Numfor Papua    which includes  the role of the government, the role of the community, the role of the private sector, the role of the media, and the role of academics who contribute and play an active role in the development process of the tourism sector.  In relation to determining  tourism  communication strategies in  revitalizing local culture in Biak Numfor Papua, establishing complementary components in the success of collaboration, including interdependence, constructive unification of thoughts to reach solutions, making decisions with all actors (Joint Ownership of Decisions) , and the existence of joint responsibility as a form of involvement that cannot run between actors if there is no cooperation and support from other factors